2010
DOI: 10.1051/0004-6361/201015082
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hydrogen fluoride absorption in diffuse molecular clouds withHerschel/HIFI: an ubiquitous tracer of molecular gas

Abstract: We discuss the detection of absorption by interstellar hydrogen fluoride (HF) along the sight line to the submillimeter continuum sources W49N and W51. We have used Herschel's HIFI instrument in dual beam switch mode to observe the 1232.4762 GHz J = 1−0 HF transition in the upper sideband of the band 5a receiver. We detected foreground absorption by HF toward both sources over a wide range of velocities. Optically thin absorption components were detected on both sight lines, allowing us to measure -as opposed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 21 publications
0
56
0
Order By: Relevance
“…The mean H 2 O/HF column density ratio in those intervals is 13.8 with a standard deviation of 0.58. The resulting H 2 O/HF ratio is thus significantly higher than that observed toward other submillimeter sources-such as W31C, W49N, and W51-where the H 2 O/HF ratio is close to unity and shows a remarkably small dispersion (Neufeld et al 2010;Sonnentrucker et al 2010). Our analysis indicates that the HF abundance along the sight line to Sgr B2(M) is similar to that inferred toward the other sources, and that the larger H 2 O/HF ratio in Sgr B2(M) reflects an enhanced H 2 O abundance along this sight line.…”
Section: Notementioning
confidence: 65%
See 3 more Smart Citations
“…The mean H 2 O/HF column density ratio in those intervals is 13.8 with a standard deviation of 0.58. The resulting H 2 O/HF ratio is thus significantly higher than that observed toward other submillimeter sources-such as W31C, W49N, and W51-where the H 2 O/HF ratio is close to unity and shows a remarkably small dispersion (Neufeld et al 2010;Sonnentrucker et al 2010). Our analysis indicates that the HF abundance along the sight line to Sgr B2(M) is similar to that inferred toward the other sources, and that the larger H 2 O/HF ratio in Sgr B2(M) reflects an enhanced H 2 O abundance along this sight line.…”
Section: Notementioning
confidence: 65%
“…Based on the average gas-phase interstellar abundance in diffuse atomic gas clouds, N F /N H = 1.8 × 10 −8 (Snow et al 2007), our observations suggest a small F depletion factor of ∼3 along the line of sight to Sgr B2(M). Neufeld et al (2010) and Sonnentrucker et al (2010) estimated similar depletion factors toward G10.6-0.4 and W49N and W51, respectively. These results corroborate the theoretical prediction that HF is the main reservoir of gas-phase fluorine in a wide variety of interstellar conditions where the HF and H 2 column densities track each other closely, with the N(HF)/2N(H 2 ) ratio equal to the gas-phase elemental abundance of F relative to H. The HF abundance obtained here, which applies to relatively diffuse gas along the sight line to Sgr B2(M), is roughly two orders of magnitude larger than that inferred by Neufeld et al (1997) from observations of the HF J = 2-1 line.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This formation mechanism is generally not very efficient, and only a small fraction of the oxygen is converted into water; the rest remains in atomic form or freezes out as water ice (Hollenbach et al 2009). Sonnentrucker et al (2010) showed that the abundance of water vapor within diffuse clouds in the Galaxy is remarkably constant, with ∼ − is the H 2 O number density relative to the total hydrogen nuclei number density. Toward the Galactic center, this value can be enhanced by up to a factor of ∼3 (Monje et al 2011;Sonnentrucker et al 2013).…”
Section: Introductionmentioning
confidence: 99%